Computational Profiling of Non-coding RNAs–viable Targets and Restorative Candidates of Influenza Viral Infection with Bioconductor Packages - Sekar, Aishwarya; Gunasekaran, Krishnasamy (Asian Journal of Biological and Life Sciences, 2020)
The advent of recent small non-coding RNA research enabled investigations of various non-coding factors like miRNAs, siRNAs and lncRNAs as post transcriptional modulators of viral pathogenesis either on a positive or negative note. Influenza A virus is responsible for contagious respiratory infection that invades the host cellular machinery to stimulate pathogenesis. The original public gene expression dataset GSE89008, from the Gene Expression Omnibus was analysed using the edgeR package and normalized log counts per million normalization. A variety of screening procedures were performed to understand the targets, miRNA transcripts, lncRNAs and the pathway enrichment. The interaction networks of the host mRNA-miRNA and lncRNA and viral siRNA- mRNA- host sense strands were constructed using the cytoscape. The study demonstrated a short list of miRNAs, which appear to be important regulators in virus–host interactions. Among them, hsa-mir-484, hsa-mir-1-3p, hsa-mir-149-5p, hsa-mir-615-3p, hsa-mir-34a-3p and hsa-mir324-3p, were shown to be highly capable of suppressing influenza infection. Transcription factors KLF41, NFYB, PLAG1, FOXO1, CEBPA and STAT1 were enhanced and may present as markers of influenza A infections. Viral-siRNAs -1534, 1537, 1538, 1540 and 1658 had great inhibitory efficacy and were predicted to silence NA, M and PA segments of viruses and suppress the viral pathogenesis by silencing the host genes most predominantly, the STAT, ELF and MAP3K genes. Elucidation of this unexpected antiviral facet of noncoding RNAs, will contribute to a better understanding of influenza–host interactions and can be established as biomarkers, or targets or therapeutic agents upon extensive research in future.
Keywords: Influenza A virus; Gene expression profiles; mRNA; Noncoding RNA; Interaction network; Transcription factors